2020
DOI: 10.7717/peerj.9502
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic characterization and genome comparison reveal insights into potential vaccine coverage and genealogy of Neisseria meningitidis in military camps in Vietnam

Abstract: Background Neisseria meningitidis remains the main cause of sporadic meningitis and sepsis in military camps in Vietnam. Yet, very limited molecular data of their genotypic and epidemiological characteristics are available from Vietnam, and particularly the military environment. Whole genome sequencing (WGS) has proven useful for meningococcal disease surveillance and guiding preventative vaccination programs. Previously, we characterized key genetic and epidemiological features of an invasive N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Pediatric populations were included in five studies. 13–17 Seven studies 12–16 , 18 , 19 reported epidemiologic outcomes ( Table 1 ) and information was identified on annual meningococcal meningitis case numbers from the Vietnam Medical Association. 20 Six studies 12 , 16 19 , 21 reported antibiotic susceptibility outcomes ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Pediatric populations were included in five studies. 13–17 Seven studies 12–16 , 18 , 19 reported epidemiologic outcomes ( Table 1 ) and information was identified on annual meningococcal meningitis case numbers from the Vietnam Medical Association. 20 Six studies 12 , 16 19 , 21 reported antibiotic susceptibility outcomes ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“… 15 Additional data on IMD serogroups were reported in three retrospective analyses of isolates from cases and/or carriers. 16 , 18 , 19 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations